Transumbilical single-site laparoscopic treatment of primary splenic cyst in child: a rare case report and review of literature - Kong, Meng; Chen, Shuai; Bai, Yuexia; Yan, Yuxi; Yi, Minggang; Wang, Meiyun; Liu, Hongzhen; Jia, Jinhua; Liu, Chuanyang; Zhang, Shisong (Frontiers in Pediatrics, 2024)
Background: Splenic cysts are relatively rare benign tumors that are asymptomatic in most patients and are usually discovered incidentally by imaging. In our case, we report a splenic cyst in a child who underwent laparoscopic partial splenectomy.Case Description: A 13-year-old boy was admitted to the hospital after an incidental finding of a splenic cyst on an abdominal ultrasound conducted 4 days prior. He was asymptomatic before admission. Upon admission, abdominal ultrasound and CT revealed a cystic lesion in the spleen, highly suspicious for a splenic cyst.Then, we used transumbilical single-site laparoscopic exploration and found a cyst measuring approximately 12 cm×11 cm×10 cm at the upper pole of the spleen, so we performed a partial splenectomy and diagnosed a primary epithelioid splenic cyst via postoperative pathology.Conclusions: Splenic cysts in children are very rare and can be treated conservatively in asymptomatic patients with a diameter of less than 5cm, while surgery is required in symptomatic patients or those with a diameter greater than or equal to 5 cm. Transumbilical single-site laparoscopic partial splenectomy is a minimally invasive and effective treatment, especially for children.